Effects of natural minor corrosion levels on mechanical property and bond anchorage behavior of CRB600H steel bars. (18th July 2022) - Chen, Meng; Qian, Hui
Highlights: The yield strength of the CRB600H steel bars with corrosion levels of 1.8% and 2.1% decreases by approximately 10% and 15%, respectively. The yield strength formula of the natural minor corrosion CRB600H steel bars was regressed. The bond toughness was taken as a reference index to study the bond behaviour. The ultimate bond strength of the natural minor corrosion CRB600H steel bars embedded in concrete was regressed. The development length of the natural minor corrosion CRB600H steel bars satisfying the reliability requirements was determined. Abstract: Mechanical property tests and bond anchorage tests of the natural minor corrosion CRB600H steel bars were carried out, and corrosion levels of the steel bars were 0.0%, 1.8%, and 2.1%, respectively. The mechanical property test results showed that the yield strength of the CRB600H steel bars with corrosion levels of 1.8% and 2.1% was approximately 10% and 15% lower than that of intact steel bars, respectively. Still, the strains at the maximum force of the two corrosion levels showed no noticeable change with intact steel bars. The yield strength formula of the natural minor corrosion CRB600H steel bars was regressed. The load-slip curves, failure modes, bond toughness, and bond strength influential factors of natural minor corrosion bond specimens were analysed in the bond anchorage tests. Compared with the control bond anchorage specimens, the bond strength of the specimens with steel bar corrosion levels of 1.8% and 2.1% decreased by 5.4% and 6.3%, respectively. The ultimate bond strength of the natural minor corrosion CRB600H steel bars embedded in concrete was regressed. The development length of the natural minor corrosion CRB600H steel bars satisfying the reliability requirements was calculated using the first-order second-moment method. Based on the calculation results, the calculation formula of the development length for the natural minor corrosion CRB600H steel bars in concrete was regressed.